Duck decoys in The Netherlands - Karelse, Désiré (Wildfowl, 2025)
The Netherlands still has most of the duck decoys of the world. Decoys were a Dutch invention, and have been known there for over 600 years. This contribution gives a concise, up-to-date account of Dutch decoys, as well as a survey of the numbers of ducks caught over the past five seasons.